1998
DOI: 10.5153/sro.1372
|View full text |Cite
|
Sign up to set email alerts
|

Recording Social Life: Reflexivity and Video Methodology

Abstract: The degree to which researcher generated visual records (for example video texts) may be used to collect valid information about the social world is subject to considerable academic debate (cf. Feld and Williams, 1975;Gottdiener, 1979 andGrimshaw, 1982). On the one hand the method is assumed, by implication, to have limited impact on the data, the taped image being treated as a replica of the unrecorded event (Vihman and Greenlee, 1987;Vuchinich, 1986). On the other, it is suggested that the video camera has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 21 publications
0
99
0
1
Order By: Relevance
“…Another threat to validity in a classroom video study concerns how the participants react to the presence of video cameras in the classroom-an issue often referred to as reactivity (C. Heath et al, 2010;Knoblauch et al, 2006;Lomax & Casey, 1998). It is a serious methodological issue to consider for researchers exploring social action in the context in which that action occurs, because the situations to be studied can be modified by the camera to greater or lesser extent (Knoblauch, Tuma, & Schnettler, 2014).…”
Section: Validitymentioning
confidence: 99%
“…Another threat to validity in a classroom video study concerns how the participants react to the presence of video cameras in the classroom-an issue often referred to as reactivity (C. Heath et al, 2010;Knoblauch et al, 2006;Lomax & Casey, 1998). It is a serious methodological issue to consider for researchers exploring social action in the context in which that action occurs, because the situations to be studied can be modified by the camera to greater or lesser extent (Knoblauch, Tuma, & Schnettler, 2014).…”
Section: Validitymentioning
confidence: 99%
“…Although it is claimed that participants are crucial to the construction of PV outputs (c.f. Haw, 2008), we want to suggest that the interests and concerns of the academic members of the research team can be equally influential and, as such, need to be reflexively acknowledged (Kindon, 2003;Lomax and Casey, 1998;Pink, 2007;Schnettler and Raab, 2008). Moreover with its capacity to review all aspects of the film-making, including un-anticipated events, dilemmas and contradictions, the research team is arguably central to developing understandings of how the process and politics of participation as well as the wider ethical concerns governing research with children might shape the production of PV data.…”
Section: Situating the Research And Its Methodological Challengesmentioning
confidence: 99%
“…Indeed, the indiscriminate and uncompromising gaze of the camera may not provide the indisputable representation of reality that is sometimes supposed (Rich et al 2000). Similarly, others (e.g., Chaplin, 1994;Lomax and Casey, 1998) have suggested that visual images and their understandings are not direct or unproblematic representations, but rather are co-created by producers and viewers. In this way, they are similar to other texts and should, therefore, be subject to the usual interpretive cautions.…”
Section: Why Video Diaries? a Contested Terrainmentioning
confidence: 99%